Autonomous cortisol secretion is associated with worse arterial stiffness and vascular fibrosis in primary aldosteronism: a cross-sectional study with follow-up data. Issue 1 (7th June 2022) - Tsai, Cheng-Hsuan; Liao, Che-Wei; Wu, Xue-Ming; Chen, Zheng-Wei; Pan, Chien-Ting; Chang, Yi-Yao; Lee, Bo-Ching; Shun, Chia-Tung; Wen, Wen-Fen; Chou, Chia-Hung; Wu, Vin-Cent; Hung, Chi-Sheng; et al.
Abstract: Objective: The presence of autonomous cortisol secretion (ACS) in patients with primary aldosteronism (PA) is common and potentially associated with poor outcomes. The aim of this study was to investigate the association between ACS and vascular remodeling in PA patients. Design and methods: We prospectively enrolled 436 PA patients from October 2006 to November 2019. ACS (defined as a cortisol level >1.8 μg/dL after a 1 mg dexamethasone suppression test) was detected in 23% of the PA patients. Propensity score matching (PSM) with age, sex, systolic and diastolic blood pressure was performed. The brachial-ankle pulse wave velocity (baPWV) was examined at baseline and 1 year after targeted treatment. Small arteries of periadrenal fat in 46 patients were stained with Picro Sirus red to quantify the severity of vascular fibrosis. Results: After PSM, the PA patients with ACS had a significantly higher prevalence of diabetes mellitus, higher plasma aldosterone concentration and higher aldosterone-to-renin ratio. The baseline mean baPWV was also significantly higher in the PA patients with ACS. After multivariable regression analysis, the presence of ACS was a significant predictor of worse baseline mean baPWV (β: 235.745, 95% CI: 59.602–411.888, P = 0.010). In addition, the PA patients with ACS had worse vascular fibrosis (fibrosis area: 25.6 ± 8.4%) compared to those without ACS (fibrosis area: 19.8 ± 7.7%, P = 0.020). After 1 year of PA treatment, baPWV significantly improved in both groups. Conclusion: The presence of ACS in PA patients is associated with worse arterial stiffness and vascular remodeling.